The relationship between spatial activity and wellbeing - related data among healthy older adults: an exploratory geographic and psychological analysis - Isaacson, Michal; Wahl, Hans-Werner (Cross-Cultural and Cross-Disciplinary Perspectives in Social Gerontology, 2017)
It has long been accepted that remaining active in later life is positively correlated with wellbeing. But is there an importance to remain spatially active in later life? This study examines data collected from participants using both questionnaires for collecting reported wellbeing indicators and GPS receivers for collecting data that describes spatial activity. An association between spatial activity, life satisfaction, perceived health and perceived physical function were found. No association between spatial activity and positive or negative affect was found. Separate analysis that was conducted for men and women revealed gender-based differences in the way that spatial activity is correlated with wellbeing. The results of this study promote a broader understanding of the importance of spatial activity in later life. Contributing to both to the theoretical aspect of activity in old age as well as having implications for considering living environments for older adults.